Literature Review: Implementation of Telerehabilitation for Patients with Eye Disorders in Middle to High-Income Countries - Nadiya Arawinda Andar; Ayu Anggraini Kusumaningrum; Pratiwi Diah Pitaloka; Dana Tri Asmara; Eka Meyliana Sugeng (Jurnal Penelitian Pendidikan IPA, 2025)
Tele-rehabilitation in eye care services is an innovative intervention solution to overcome geographical limitations and improve accessibility to rehabilitation services. This study aims to examine the implementation of telerehabilitation in patients with eye disorders in various countries, especially in low to high-income countries. This study is a narrative literature review of 3 journal databases, namely PubMed, ScienceDirect, and Google Scholar. Data screening was conducted using Rayyan.ai. Selected articles were then assessed for eligibility using the Mixed-Method Appraisal Tool (MMAT) with a minimum score of 80 points. Articles that passed the MMAT assessment were then analyzed and synthesized before being categorized to obtain themes from the implementation of eye care telerehabilitation in various countries. The screening resulted in 12 articles that met the criteria in this study. The results of the study showed that telerehabilitation is effective in improving access to rehabilitation services, especially in remote areas. Tele-rehabilitation has also been proven to improve the quality of life of patients through improved visual skills, independence, and mental well-being. However, the implementation of telerehabilitation still faces challenges such as limited access to technology, lack of digital skills, and unstable internet connectivity. Tele-rehabilitation has great potential to improve access and quality of life for patients with eye disorders. Although there are several challenges, with adequate technological infrastructure support and comprehensive training, telerehabilitation can be a sustainable solution to improve eye health services. Future research needs to focus on developing more personalized interventions, long-term evaluation, and addressing the digital divide.